Concurrent use of opioids with benzodiazepines or nonbenzodiazepine sedatives among patients with cancer referred to an outpatient palliative care clinic. Issue 24 (28th August 2019) - Haider, Ali; Azhar, Ahsan; Nguyen, Kristy; Dev, Rony; Naqvi, Syed Mujtaba Ali; Naqvi, Syed Mussadiq Ali; Edwards, Tonya; Reddy, Akhila; Dalal, Shalini; Tanco, Kimberson C.; Arthur, Joseph; Williams, Janet L.; et al.
Abstract : Background: The concurrent use of opioids with benzodiazepines (BZD) or nonbenzodiazepine sedatives (S) recently was found to be associated with an increased risk of overdose death compared with the use of opioids alone. In the current study, the authors examined the frequency and trend of concurrent opioid/BZD‐S use and its associated risk factors among patients with cancer. Methods: Data regarding the frequency and trend of concurrent opioid/BZD‐S use were extracted for 1500 randomly selected patients referred to the outpatient palliative care clinic at The University of Texas MD Anderson Cancer Center between the calendar years of 2011 and 2016. To explore associated risk factors, the authors compared the demographic and clinical predictors of 418 patients each in the concurrent opioid/BZD‐S group and opioids‐only group. Results: In 2011, at the time of referral to the palliative care clinic, 96 of 221 patients with cancer (43%) were prescribed concurrent opioids/BZD‐S. This rate progressively declined to 67 of 217 patients (31%) by 2016 ( P  = .0008). Patients in the concurrent opioid/BZD‐S group had a higher percentage of females (233 individuals; 55% [ P  = .007]) and whites (323 individuals; 77% [ P  = .002]), and patients reported higher scores regarding depression ( P  = .0001), anxiety ( P  ≤ .0001), drowsiness ( P  = .048), and worst feeling of well‐being ( P  = .001). The morphine equivalent daily dose was significantly higher in concurrent opioid/BZD‐S group (median of 67.5 mg/day [interquartile range (IQR), 30‐135 mg/day] vs 60 mg/day [IQR, 30‐105 mg/day]; P  = .034). Multivariate analysis demonstrated that anxiety ( P  ≤ .0001), white race ( P  = .0092), and poor Eastern Cooperative Oncology Group performance status ( P  = .0017) were significantly associated with concurrent use. Conclusions: The concurrent use of opioids with BZD‐S has declined but continues to be frequent among patients with cancer. Anxiety, white race, and poor Eastern Cooperative Oncology Group performance status were associated with its use. More research is needed to explore which medications can replace these agents. Abstract : The concurrent use of opioids with benzodiazepine sedatives has declined, but continues to be frequent among patients with cancer. More research is needed to explore which medications can replace these agents.